Controlling structural and magnetic properties of IONPs by aqueous synthesis for improved hyperthermia. Issue 22 (24th February 2017) - Bonvin, Debora; Arakcheeva, Alla; Millán, Angel; Piñol, Rafael; Hofmann, Heinrich; Mionić Ebersold, Marijana
Abstract : Introducing a hydrothermal step after coprecipitation leads to iron oxide nanoparticles with higher vacancy ordering, saturation magnetization and specific absorption rate. Abstract : Iron oxide nanoparticles (IONPs) were synthesized by a novel aqueous synthesis route which combines co-precipitation (CP) and hydrothermal (HT) treatment, termed CP + HT, and compared with IONPs obtained by the standard CP method. Properties of both types of IONPs, including their morphology, diameters, composition, structure and crystallinity, as well as magnetic properties and toxicity were studied and correlated with the synthesis route. Their potential application as mediators for hyperthermia treatment has been evaluated by the specific absorption rate (SAR). Studies showed that IONPs obtained by a novel CP + HT route have a more controlled morphology, structure and crystallinity, leading to better magnetic properties and SAR as compared to IONPs synthesized by CP. Reported IONPs are also not toxic as shown by two assays in two cell lines. These results suggest that our IONPs are suitable for biomedical applications, especially as mediators for the hyperthermia treatment.